Pengaruh Pendidikan Berbasis Karakter Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa Smp Pgri 12 Jakarta Selatan - Hugo Aries Suprapto (Universitas Mathla'ul Anwar Banten, 2017)
Improving the quality of education and improvement of character human resources is crucial in enhancing the nation's competitiveness through innovation to do a good learning. The research aims to develop character-based education that is being integrated with innovative learning methods to improve the activity and learning outcomes of economic subjects in SMP PGRI 12 South Jakarta. The results showed that the character-based education can help students in learning to achieve competency in accordance with the demands of the curriculum. Character-based education as a learning medium can increase the activity and learning outcomes of economic subjects easily and efficiently so that the interaction of students' understanding of economic study, and at the same time improve the character of the students. Students are very interested in studying economic subjects to become entrepreneurs with good character education. Gutru expected to be able to use the character-based pembelajarn methods with innovation to enhance the activity and learning outcomes of economic subjects